Community‐based distribution of misoprostol to prevent postpartum haemorrhage at home births: results from operations research in rural Ghana. (28th November 2013) - Geller, S; Carnahan, L; Akosah, E; Asare, G; Agyemang, R; Dickson, R; Kapungu, C; Owusu‐Ansah, L; Robinson, N; Mensah‐Homiah, J
<x xml:space="preserve">Abstract</x> Objective To report on a rigorous distribution and monitoring plan to track misoprostol for community‐based distribution to reduce postpartum haemorrhage (PPH) in rural Ghana. Design Operations research. Setting Rural Ghana. Sample Women in third trimester of pregnancy presenting to primary health centres (PHCs) for antenatal care (ANC). Methods Ghana Health Service (GHS), Millennium Village Projects, and the University of Illinois at Chicago conducted an operations research study designed to assess the safety, feasibility, and acceptability of community‐based distribution of misoprostol to prevent PPH at home deliveries in rural Ghana. One thousand doses (3000 tablets, 200 μg each) were obtained from the Family Health Division of GHS. Three 200‐μg tablets of misoprostol (600 μg) in foil packets were packaged together in secured transparent plastic packets labelled with pictorial messages and distributed to midwives at seven PHCs for distribution to pregnant women. Main outcome measures Correct use of misoprostol in home deliveries and retrieval of unused misoprostol doses, PPH rates and maternal mortality. Results Of the 999 doses distributed to midwives, 982 (98.3%) were successfully tracked, with a 1.7% lost to follow‐up rate. Midwives distributed 654 doses to women at third‐trimester ANC visits. Of women who had misoprostol to use at home, 81% had an institutional delivery and were able to return the misoprostol safely to the midwife. Of the women that used misoprostol, 99% used the misoprostol correctly. Conclusions This study clearly demonstrates that misoprostol distributed antenatally to pregnant women can be used accurately and reliably by rural Ghanaian women, and should be considered for policy implementation across Ghana and other countries with high home birth rates and maternal mortality ratios.